Street Vendors’ Survival Strategies at Simpang Lima Semarang During the Crisis and After the Monetary Crisis of 1998-2003 - Zanuba Nur Arifah Chafsof; Bambang Rakhmanto (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This article examines how and why street vendors at Simpang Lima in Semarang were able to continue operating amid the 1998 monetary crisis and the post-crisis period through 2003. This study applies critical history within a socio-economic framework. Critical history, in this context, is understood as a historiographical approach that does not merely reconstruct past events but also provides in-depth analysis of historical sources through heuristic stages source criticism, interpretation, and historiography to better understand socio-economic dynamics. Research sources were collected from newspaper archives and relevant local government documents and then analyzed within their respective contexts. The findings indicate that the resilience of street vendors was driven by various adaptive strategies, such as flexibility in economic activities, adjustments to production and distribution patterns, the utilization of social networks, and negotiation skills regarding urban regulatory policies. These findings position street vendors as informal economic actors who play an active role in responding to pressures caused by the economic crisis. This study contributes to the historical analysis of the 1998 crisis by emphasizing the economic experiences of informal groups within the context of urban history in Indonesia.